2016
DOI: 10.1016/j.puhe.2016.04.012
|View full text |Cite
|
Sign up to set email alerts
|

Exploratory study of the role of knowledge brokers in translating knowledge to action following global maternal and newborn health technical meetings

Abstract: Findings on knowledge use and sharing suggest that most respondents saw themselves as knowledge brokers or intermediaries in a position to influence the translation of knowledge into action in health policy and practices in their countries. Results suggest that supporting knowledge brokers working in a local and regional context to spur change, as described in the paper, has the potential to improve health outcomes. Further research is needed to isolate specific interventions and their knowledge translation ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 14 publications
1
25
0
1
Order By: Relevance
“…The findings from our mixed-method study show that the Canadian samples of self-identified KBs describe their roles and skills in ways consistent with existing literature [2,7,10,11,22]; that is, as our qualitative data have shown, KBs build relationships that enable knowledge users to gain access to research evidence that can inform or improve their practices. Against this backdrop, both our qualitative and quantitative data suggest, at least among the KBs in our study, that the use of theories and frameworks to guide knowledge brokering varies.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…The findings from our mixed-method study show that the Canadian samples of self-identified KBs describe their roles and skills in ways consistent with existing literature [2,7,10,11,22]; that is, as our qualitative data have shown, KBs build relationships that enable knowledge users to gain access to research evidence that can inform or improve their practices. Against this backdrop, both our qualitative and quantitative data suggest, at least among the KBs in our study, that the use of theories and frameworks to guide knowledge brokering varies.…”
Section: Discussionsupporting
confidence: 82%
“…In such situations, where knowledge is transferred to users without being mobilised in routine practice, KBs need to identify and meet clients' needs to better support evidence-based decision-making at the organisational and policy levels [21]. Similarly, Norton et al [22] suggest that drawing on multiple theoretical frameworks can inform the function and roles of KBs, what kinds of evidence might be required, and what mechanisms of knowledge synthesis might be deployed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Knowledge Translation (KT) – which goes by a host of different terms [ 4 , 5 ] - describes the process of using evidence to make decisions and create action [ 6 ]. A commonly used definition of KT is the Canadian Institutes of Health Research’s: “ A dynamic and iterative process that includes synthesis, dissemination, exchange and ethically-sound application of knowledge to improve [health]….…”
Section: Introductionmentioning
confidence: 99%
“…Also, ongoing conversations among KBs and their peers seem to have a number of advantages at the inner setting level when communicating with clinical teams and managers (e.g., decreasing the resistance to change and providing the informal evaluation for KBs activities) and at the outer settings level when communicating with professional and provincial groups (e.g., facilitating the accessibility to information). The existing literature [89][90][91][92][93] and a recent mixed-method study [94] showed that by building relationships with knowledge users Canadian KBs' help their peers to gain access to research evidence that can inform or improve their practices. Previous research also emphasized the importance of interpersonal communication as a substantial element in knowledge brokering; communication acts as a foundation to build relationships of trust between KBs and their working teams [10,54,76,90,95].…”
Section: Organizational Levelmentioning
confidence: 99%